PARTISIPASI AYAH DALAM PENGASUHAN DENGAN PERKEMBANGAN ANAK USIA 12 – 24 BULAN - Niki Astria; Parniah; Dwi Rahmawati (Jambi Medical Journal : Jurnal Kedokteran dan Kesehatan, 2023)
Background: The presence of a father in parenting is as important as a mother. Only 3.9% of fathers' participation in parenting has an impact on the progress of children's development. The involvement of fathers in child care is very supportive of the growth and development of children and has a positive impact on children. Objectives: The purpose of this study was to analyze the relationship between father's participation in parenting and the development of children aged 12-24 months in Pulau Tengah Village, Muara Madras Health Center Region. Method: This research is an analytic study with a cross-sectional study design. The sample in this study was fathers who have children aged 12-24 months, totaling 66 people. This research was carried out in the village of Pulau Tengah, the area of â€‹â€‹the Muara Madras Public Health Center, Merangin Regency, Jambi Province. Data analysis using Fisher Exact test. Results: The results showed that 56.1% of father's participation in parenting, 87.9% of normal development of children aged 12-24 months. There is a significant relationship between father's participation in parenting and the development of children aged 12-24 months, the value is 0.018 (Ï<0.05). Conclussion There are many positive benefits with the involvement of fathers in parenting to improve child development, for that health workers should be able to provide correct and clear information or education that is easily understood by the community about the importance of father involvement in child care so that child care is not only the duty of the mother but also the mother work with parents. Keywords: Father's participation; Child development